Laccase kinetics of degradation and coupling reactions - Zille, Andrea (2005)
The ability of Trametes villosa laccase to degrade an azo dye (methyl orange) and to catalyze the coupling reactions between the aromatic amines and catechol was studied. It was found that the apparent Michaelis–Menten constants obtained from amperometric measurements were comparable to the ones obtained in the oxygen consumption experiments (8.20 and 7.40 µM, respectively). From the measurements of the mediated and mediatorless currents of azo dye degradation and coupling reactions itwas concluded that the addition of 1-hydroxybenzotriazole (HBT) as mediator considerably improves the catalytic efficiencies. It can be concluded that the mediated coupling of the aromatic amine with catechol opens the perspectives of physical removal of these polluting chemicals from the nature and the usage of the laccase immobilized onto macro-electrodes in online systems with continuous monitoring of the enzyme activity.